Aqueous lithium ion battery electrolyte and preparation method thereof
By using nitrile solvents containing benzene ring functional groups as co-solvents in the electrolyte of water lithium-ion battery, the hydrogen bond network between water molecules is broken, and the problem of narrowing the electrochemical stability window and hydrogen evolution reaction is solved, the electrochemical stability window is broadened and the inhibition of hydrogen evolution reaction is achieved, and the overall performance of the battery is improved.
Patent Information
- Application Number
- CN202510282211.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-11
- Publication Date
- 2025-04-29
AI Technical Summary
The electrochemical stability window of existing water-based lithium-ion battery electrolytes is narrow, and it is prone to hydrogen and oxygen evolution side reactions, which limits its output voltage and energy density. The selection of co-solvents lacks effective ideological guidance and screening principles, making it difficult to fully meet the needs of high-performance electrolytes.
The nitrile solvent containing benzene ring functional groups is used as a co-solvent. Through its multi-site hydrogen bond receptor and benzene ring hydrophobic properties, the synergistic mechanism breaks the hydrogen bond network between water molecules, inhibits the activity of free water, thereby broadening the window of electrochemical stability and inhibiting the hydrogen evolution reaction.
The electrochemical stability window of the aqueous electrolyte is widened, which significantly inhibits the hydrogen evolution reaction, improves the interface stability and cycle stability, and is suitable for large-scale mass production.
Smart Images

Figure CN119905687A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an aqueous lithium ion battery electrolyte and a preparation method thereof, belonging to the technical field of lithium secondary batteries. Background Art
[0002] Lithium-ion batteries are widely used in portable electronic devices, electric vehicles, and energy storage systems due to their high energy density and long life. Traditional lithium-ion batteries mainly use organic electrolytes. Due to their shortcomings such as flammability and volatility, they are prone to thermal runaway of batteries under overcharge, short circuit or high temperature conditions, which seriously threatens safety of use. Aqueous electrolytes have become a promising energy storage technology due to their advantages such as low cost, high safety, high ionic conductivity, and environmental friendliness. However, aqueous electrolytes have a narrow electrochemical stability window (about 1.23V) and are prone to hydrogen and oxygen evolution side reactions at high voltages, which limits their output voltage and energy density. In addition, side reactions such as dissolution of electrode materials, proton co-intercalation reactions, and current collector corrosion are also important reasons that limit the application of aqueous batteries in the field of high energy density energy storage. Therefore, it is crucial to develop aqueous electrolytes with high safety, low cost, and a wide electrochemical stability window.
[0003] High-concentration aqueous electrolytes have significant effects in broadening the electrochemical stability window, inhibiting side reactions and improving cycle stability, but they are expensive. And as the concentration increases, the viscosity of the electrolyte increases, resulting in a decrease in ionic conductivity, which is not only inconsistent with the original design intention of aqueous batteries, but also has certain limitations in practical applications. In recent years, introducing organic solvents (dimethyl sulfoxide, succinonitrile, polyethylene glycol, etc.) as co-solvents into aqueous electrolytes has become the main way to broaden the electrochemical window. These organic co-solvents usually have special functional groups that can act as hydrogen bond acceptors (donors), interact with water molecules through strong hydrogen bonds, destroy the hydrogen bond network within the water molecules, and reduce the activity of water molecules. In addition, the addition of some high dielectric constant organic solvents can increase the solubility of lithium salts and increase the migration rate of lithium ions. The team led by Professor Lu Yijun of the Chinese University of Hong Kong has developed a "molecular crowding" electrolyte. By introducing water-miscible polyethylene glycol (PEG) as a crowding agent, the water activity was significantly reduced at a lower salt concentration (2m LiTFSI), and the electrochemical stability window was widened to 3.2V. The electrolyte effectively inhibits the hydrogen / oxygen evolution reaction and improves the interface stability by reducing the number of free water molecules and hydrogen bonds.
[0004] However, the selection of co-solvents is still in the trial and error stage, lacking effective ideological guidance and screening principles. It is still difficult to fully meet the needs of aqueous batteries for high-performance electrolytes in terms of lithium salt solubility, lithium ion solvation regulation ability, and electrochemical stability. Therefore, it is urgent to explore an efficient and universal design concept to achieve the functional selection of co-solvents, thereby further broadening the voltage window of aqueous electrolytes and significantly improving the overall performance of aqueous batteries. Summary of the invention
[0005] The purpose of the present invention is to provide an aqueous lithium ion battery electrolyte and a preparation method thereof.
[0006] The aqueous lithium-ion battery electrolyte of the present invention is an electrolyte obtained by mixing lithium salt, water and benzonitrile solvents. The present invention proposes a co-solvent selection principle, which uses a nitrile solvent containing a benzene ring functional group, utilizes its multi-site hydrogen bond receptor and the hydrophobic properties of the benzene ring, and effectively destroys the hydrogen bond network between water molecules through a synergistic mechanism, thereby inhibiting the activity of free water. The benzonitrile organic solvent containing a -C≡N functional group interacts with H2O to produce intermolecular hydrogen bonds, breaking the tetrahedral hydrogen bond network structure inside the water molecule, thereby effectively reducing the activity of Li + The content of water molecules in the solvent sheath. In addition, the hydrophobic properties of the benzene ring functional groups in benzonitrile solvents enable them to form a hydrophobic protective layer on the electrode surface or in the electrolyte, effectively isolating the direct contact between water molecules and the electrode. The synergistic effect of the two functional groups broadens the electrochemical stability window of the aqueous electrolyte and significantly inhibits the hydrogen evolution reaction.
[0007] The preparation process of the aqueous electrolyte of the present invention is simple, conventional equipment is used, raw materials are easily available, and the preparation process is safe and pollution-free, and the aqueous electrolyte is suitable for large-scale batch production.
[0008] The present invention is achieved through the following technical solutions.
[0009] The invention provides an aqueous lithium-ion battery electrolyte, which is prepared by mixing lithium salt, water and a benzonitrile solvent.
[0010] In the above electrolyte, the mass molar concentration of the lithium salt in the electrolyte may be 0.1 to 5 m (ie 0.1 to 5 mol / kg).
[0011] The molar mass ratio of the water to the benzonitrile solvent may be 0.1:1 to 3:1.
[0012] In the above-mentioned electrolyte, the lithium salt is selected from at least one of LiPF6, LiN(SO2CF3)2, LiCF3SO3, LiC(SO2CF3)3, LiBOB, LiMOB, LiBMB, and LiODFB.
[0013] In the present invention, the benzonitrile organic solvent is selected from one or more of benzonitrile, o-fluorobenzonitrile, p-fluorobenzonitrile, phenoxyacetonitrile, terephthalonitrile and m-trifluoromethylbenzonitrile.
[0014] The method for preparing the above-mentioned electrolyte provided by the present invention comprises the following steps:
[0015] (1) In an inert atmosphere, a benzonitrile solvent is mixed with ultrapure water to obtain a mixed solvent;
[0016] (2) In the inert atmosphere, the lithium salt is mixed with the mixed solvent to obtain a mixed electrolyte for an aqueous lithium ion battery.
[0017] In the above-mentioned preparation method, the inert atmosphere is nitrogen or argon with a purity of not less than 99% (or an O2 content of <1 ppm).
[0018] The aqueous lithium-ion battery electrolyte disclosed in the present invention is used in preparing aqueous lithium-ion batteries.
[0019] In the above application, the positive electrode active material of the aqueous lithium-ion battery is LiCoO2, LiMn2O4, LiFePO4
[0020] 、LiNi 0.5 Mn 1.5 O4 or Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2, the negative electrode active material is NbO2 or Li4Ti5O 12 .
[0021] In the above application, the ambient temperature of the test of the aqueous lithium-ion battery electrolyte and the aqueous lithium-ion battery can be -30°C to 30°C.
[0022] The present invention further provides an aqueous lithium ion battery, the aqueous lithium ion battery comprising a positive electrode, a negative electrode and an electrolyte;
[0023] The active material of the positive electrode is LiCoO2, LiMn2O4, LiFePO4, LiNi 0.5 Mn 1.5 O4 or Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2, the active material of the negative electrode is NbO2 or Li4Ti5O 12 ;
[0024] The electrolyte is the aqueous lithium-ion battery electrolyte mentioned above.
[0025] In the above aqueous lithium-ion battery, the ambient temperature for testing the full cell of the aqueous lithium-ion battery may be -30 to 30°C.
[0026] In a specific example, the assembly of the full battery of the aqueous lithium-ion battery is as follows: in a glove box filled with argon (O2 <1ppm), the electrode plate, aqueous electrolyte and gasket, and spring are placed in the 2025 button battery blank in the order of negative electrode shell-spring-gasket-negative electrode plate-electrolyte-diaphragm-positive electrode plate-positive electrode shell, and assembled into a full battery, and then the two battery shells are compacted and fastened with a sheet press to obtain a test button battery. The thickness of the gasket is 1mm, and the model of the diaphragm is glass fiber GF / F.
[0027] The present invention has the following advantages:
[0028] (1) The electrolyte of the present invention breaks the tetrahedral hydrogen bond network structure inside the water molecule through the hydrogen bond interaction between the -C≡N functional group in the benzonitrile solvent and H2O, inhibits the activity of H2O, and reduces the Li + The water content in the solvent sheath expands the electrochemical stability window of the aqueous electrolyte.
[0029] (2) The electrolyte of the present invention utilizes the hydrophobicity of the benzene ring in the benzonitrile solvent to form a hydrophobic protective layer on the electrode surface or in the electrolyte, effectively isolating the direct contact between water and the electrode.
[0030] (3) The preparation method of the aqueous electrolyte described in the present invention is simple, easy to operate, environmentally friendly, and the raw materials are readily available, making it suitable for industrial applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is the electrochemical window diagram of the mixed liquid electrolyte prepared in Example 1.
[0032] Figure 2 This is the cycle capacity-efficiency diagram of the full battery assembled with the mixed liquid electrolyte prepared in Example 1 at 30°C.
[0033] Figure 3 TEM image of the negative electrode surface after full electrical cycle of the mixed liquid electrolyte prepared in Example 1.
[0034] Figure 4 The mass spectrum (DEMS) of the hydrogen changes during the first charge and discharge of the full battery assembled with the mixed liquid electrolyte prepared in Example 2 and the corresponding charge and discharge curve diagram.
[0035] Figure 5 This is the cycle capacity-efficiency diagram of the full battery assembled with the mixed liquid electrolyte prepared in Example 3 at 30°C. DETAILED DESCRIPTION
[0036] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0037] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0038] In the following embodiments, the assembly of an aqueous lithium-ion full battery is as follows: in a glove box filled with argon (O2 <1ppm), the electrode plate, aqueous electrolyte and gasket, and spring are placed in a 2025-type button battery blank in the order of negative electrode shell-spring-gasket-negative electrode plate-electrolyte-diaphragm-positive electrode plate-positive electrode shell to assemble into a full battery, and then the two battery shells are compacted and fastened with a sheet press to obtain a test button battery. The thickness of the gasket is 1mm, and the model of the diaphragm is glass fiber GF / F.
[0039] After the assembled full battery was left to rest for 24 h, the electrochemical performance test was carried out: the electrochemical window test was carried out on an electrochemical workstation (Ivium-Start, Ivium-N-Stat, the Netherlands) with a scan rate of 5 mV / s; the battery charge and discharge test was carried out using a Xinwei battery tester (model BTS-5V10mA, Shenzhen Xinwei Electronics Co., Ltd.) with a test rate of 6C or 10C; the battery gas production was analyzed using an electrochemical mass spectrometer (Hiden PHR20, Beijing Ingelhead Analytical Technology Co., Ltd.).
[0040] Embodiment 1:
[0041] (1) In a glove box filled with argon gas with a purity of greater than or equal to 99%, 6.2 g of phenoxyacetonitrile and 0.3 g of ultrapure water (i.e., the molar ratio of water to phenoxyacetonitrile is 0.358:1) are first dissolved and stirred for 1 h to obtain a water-benzonitrile mixed solvent.
[0042] (2) 3.4 g of LiN(SO2CF3)2 was dissolved in the mixed solvent of step (1) and stirred at room temperature for 12 h to obtain 2 mL of a water-benzonitrile-based mixed electrolyte for lithium-ion batteries.
[0043] The mixed liquid electrolyte prepared in this example was subjected to an electrochemical window test using an Ivium-Start electrochemical workstation, using a three-electrode system, with working electrodes of Pt (positive electrode side) and Al (negative electrode side), a counter electrode of activated carbon (AC), and a reference electrode of Ag / AgCl electrode, with a scan rate of 5 mV / s. Figure 1 It can be seen that the aqueous lithium-ion battery of the present invention uses a water-benzonitrile electrolyte to achieve a wide electrochemical window of 0.15 to 5.25 V, which meets the requirements of LiMn2O4 (4.0 V vs. Li + / Li) and Li4Ti5O 12 (1.55V vs.Li + / Li) can be reversibly inserted and deintercalated.
[0044] The mixed liquid electrolyte prepared in this example is mixed with LiMn2O4-Li4Ti5O 12 The positive electrode and negative electrode active materials (i.e., the same below) were assembled into a full battery and tested at 30°C using the Xinwei electrochemical testing system. In the battery cycle performance test, the charge and discharge current size was based on the Li4Ti5O 12 The mass of the active material of the negative electrode and its theoretical capacity of 175 mAh / g are calculated and set. 12 The charging and discharging voltage range of the full battery is 1-2.8V. Figure 2 The test shows that the full battery prepared by the water-benzonitrile electrolyte of the aqueous lithium-ion battery of the present invention can be stably cycled for 500 weeks at a rate of 6C, with a discharge capacity of 128.8 mAh / g in the first week and a discharge capacity of 99.6 mAh / g after 500 charge and discharge cycles, a capacity retention rate of 77.3%, and an average coulombic efficiency of >99%. Figure 3 TEM test shows that the SEI film generated by the water-benzonitrile mixed electrolyte for the lithium-ion battery of the present invention is evenly distributed, can act as an electron barrier, prevent water molecules from decomposing, and effectively protect the electrode, so the battery has good cycle stability.
[0045] Embodiment 2:
[0046] (1) In a glove box filled with argon gas with a purity greater than or equal to 99%, 5.7 g of benzonitrile and 0.3 g of ultrapure water (i.e., the molar ratio of water to benzonitrile is 0.286:1) are first dissolved and stirred for 1 h to obtain a water-benzonitrile mixed solvent.
[0047] (2) 3.4 g of LiN(SO2CF3)2 was dissolved in the mixed solvent of step (1) and stirred at room temperature for 12 h to obtain 2 mL of a water-benzonitrile-based mixed electrolyte for lithium-ion batteries.
[0048] The mixed liquid electrolyte prepared in this embodiment is mixed with LiMn2O4 positive electrode sheet, Li4Ti5O 12 The negative electrode sheets were assembled into a full battery in an electrochemical reaction cell and tested using a Hiden PHR20 electrochemical mass spectrometer. Figure 4 It can be seen that the full battery LiMn2O4-Li4Ti5O prepared by the aqueous lithium-ion battery of the present invention using water-benzonitrile electrolyte 12 During the first week of charge and discharge, only a small amount of hydrogen was generated, indicating that the decomposition of H2O on the anode surface in the mixed liquid electrolyte prepared in this embodiment was effectively suppressed.
[0049] Embodiment 3:
[0050] (1) In a glove box filled with argon gas with a purity of greater than or equal to 99%, 6.2 g of phenoxyacetonitrile and 0.3 g of ultrapure water (i.e., the molar ratio of water to phenoxyacetonitrile is 0.358:1) are first dissolved and stirred for 1 h to obtain a water-benzonitrile mixed solvent.
[0051] (2) 2.2 g of LiN(SO2F)2 was dissolved in the mixed solvent of step (1) and stirred at room temperature for 12 h to obtain 2 mL of a water-benzonitrile-based mixed electrolyte for lithium-ion batteries.
[0052] The mixed liquid electrolyte prepared in this example is mixed with LiMn2O4-Li4Ti5O 12 Assemble into a full battery and follow
[0053] The electrochemical performance test was carried out in the same manner as in Example 1 of the present invention. The battery charge and discharge performance test conditions were: the battery was tested at 30°C using a Xinwei electrochemical test system. In the battery cycle performance test, the charge and discharge current was based on the Li4Ti5O 12 The mass of the active material of the negative electrode and its theoretical capacity of 175 mAh / g are calculated and set. Figure 5 It can be seen from the test results that the full battery prepared by the high-stability benzonitrile solvent aqueous lithium-ion battery electrolyte of the present invention has a discharge specific capacity of about 60.3 mAh / g after 500 cycles at a high rate of 10C, an average coulombic efficiency of >98%, and has good cycle stability.
[0054] In summary, the above are only preferred embodiments of the present invention and are not intended to limit the protection scope of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. An aqueous lithium-ion battery electrolyte and a preparation method thereof, characterized in that: The electrolyte is an electrolyte obtained by mixing lithium salt, water and a benzonitrile organic solvent; It has a wide electrochemical stability window and excellent cycle stability.
2. The aqueous lithium-ion battery electrolyte according to claim 1, characterized in that: The lithium salt is one or more of LiPF6, LiN(SO2CF3)2, LiCF3SO3, LiC(SO2CF3)3, LiBOB, LiMOB, LiBMB, and LiODFB.
3. The aqueous lithium-ion battery electrolyte according to claim 1, characterized in that: The organic solvent contains an organic compound having a benzene ring and a nitrile group.
4. The aqueous lithium-ion battery electrolyte according to claim 3, characterized in that: The organic solvent is one or more of benzonitrile, o-fluorobenzonitrile, p-fluorobenzonitrile, phenoxyacetonitrile, terephthalonitrile and m-trifluoromethylbenzonitrile.
5. A method for preparing an aqueous lithium-ion battery electrolyte according to any one of claims 1 to 4, characterized in that: The method steps are as follows: (1) in a glove box filled with protective gas, dissolving a benzonitrile solvent and water in a certain proportion and stirring them to obtain a water-benzonitrile mixed solvent; (2) in a glove box filled with protective gas, dissolving lithium salts of different concentrations in a water-benzonitrile solvent, mixing and stirring to obtain a water-benzonitrile mixed electrolyte; The protective gas is nitrogen or argon with a purity of not less than 99%.
6. The method for preparing an aqueous lithium-ion battery electrolyte according to claim 5, characterized in that: In the electrolyte, the molar concentration of lithium salt dissolved in the mixed solvent can be 0.1 to 5 mol / kg; the molar mass ratio of water to benzonitrile solvent is 0.1:1 to 3:
1.
7. An application of the aqueous lithium-ion battery electrolyte according to claims 1-4, characterized in that: The water-benzonitrile mixed electrolyte is applied to an aqueous lithium-ion battery system.
8. The use of the aqueous lithium-ion battery electrolyte according to claim 7, characterized in that: The aqueous lithium-ion battery system is LiMn2O4-NbO2, LiCoO2-Li4Ti5O 12 、LiMn2O4-Li4Ti5O 12 、LiFePO4-Li4Ti5O 12 , Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2-Li4Ti5O 12 or LiNi 0.5 Mn 1.5 O4-Li4Ti5O 12 system.
9. The use of the aqueous lithium-ion battery electrolyte according to claim 8, wherein the ambient temperature for the electrolyte and full battery testing is -30°C to 30°C.